Kedudukan Hukum Pembagian Harta Warisan pada Perempuan di Minangkabau dengan Sistem Matrilineal Ditinjau dari Hukum Islam - Salsabilla Putri Ananda; Husni Syawali (UNISBA Press, 2024)
ABSTRACT The Minangkabau kinship system, which adheres to a matrilineal descent, especially in the context of inheritance division, presents a unique situation due to the differences between Minangkabau customary law, which values female heirs, and the Islamic inheritance law, which is bilateral. Despite the philosophy of